Integration of gene expression and brain-wide connectivity reveals the multiscale organization of mouse hippocampal networks. (November 2018) - Bienkowski, Michael; Bowman, Ian; Song, Monica; Gou, Lin; Ard, Tyler; Cotter, Kaelan; Zhu, Muye; Benavidez, Nora; Yamashita, Seita; Abu-Jaber, Jaspar; Azam, Sana; Lo, Darrick; et al.
Abstract Understanding the organization of the hippocampus is fundamental to understanding brain function related to learning, memory, emotions, and diseases such as Alzheimer's disease. Physiological studies in humans and rodents have suggested that there is both structural and functional heterogeneity along the longitudinal axis of the hippocampus. However, the recent discovery of discrete gene expression domains in the mouse hippocampus has provided the opportunity to re-evaluate hippocampal connectivity. To integrate mouse hippocampal gene expression and connectivity, we mapped the distribution of distinct gene expression patterns in mouse hippocampus and subiculum to create the Hippocampus Gene Expression Atlas (HGEA). Notably, previously unknown subiculum gene expression patterns revealed a hidden laminar organization. Guided by the HGEA, we constructed the most detailed hippocampal connectome available using Mouse Connectome Project (http://www.mouseconnectome.org ) tract tracing data. Our results define the hippocampus' multiscale network organization and elucidate each subnetwork's unique brain-wide connectivity patterns. Bienkowski et al. have created a new subregional atlas of the mouse hippocampus that integrates gene expression with anatomical connectivity to reveal the multiscale organization of the hippocampus and its connections throughout the brain.